BURNOUT BEHIND THE REPORTS: AUDITING THE MENTAL HEALTH AND PERSONALITY TYPES OF AUDITORS AMID DEADLINE PRESSURE - Nabiilah Putri; Yusnaini Yusnaini (Jurnal Media Akademik (JMA), 2026)
Auditors face intense occupational pressures that jeopardise their psychological well-being and, by extension, the quality of audit work. This article examines the interplay between burnout and personality types among auditors operating under deadline pressure. Through a Systematic Literature Review of 40 Scopus- and SINTA-indexed publications spanning 2021 to 2025, this study synthesises empirical evidence on how emotional exhaustion, cynicism, and reduced professional efficacy the three core dimensions of occupational burnout interact with personality traits such as neuroticism, conscientiousness, and extraversion to shape auditor judgement. Drawing on Conservation of Resources Theory (Hobfoll, 1989), the Burnout Model proposed by Maslach et al. (2001), and the Big Five personality framework (McCrae & Costa, 1987), the findings reveal that burnout significantly impairs professional scepticism and heightens dysfunctional audit behaviour. Personality type moderates this relationship: auditors high in neuroticism are most susceptible to burnout, whereas those high in conscientiousness demonstrate greater psychological resilience. Organisational factors including time budget pressure, workload intensity, and supervisory support further amplify or attenuate these effects. The study concludes that improving audit quality requires systematic attention to psychological risk factors through personality-informed human resource management and employee well-being programmes.